Semiconductor protective film and coating process thereof

By optimizing the material ratio and coating process in the semiconductor protective film, the heat dissipation and heat shrinkage problems of traditional protective films are solved, and higher thermal conductivity and stress buffering capabilities are achieved, which significantly improves the performance stability of semiconductor devices and Service life.

CN119161771AActive Publication Date: 2024-12-20GUANGDONG RUIDETAI TECHNOLOGY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411286209.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-20
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

Traditional semiconductor protective films have defects in heat dissipation and heat shrinkage performance, and are unable to effectively dissipate heat and adapt to temperature changes, resulting in temperature increase, performance degradation and mechanical stress, affecting stability and reliability.

Method used

Using a semiconductor protective film and its coating process, including a base layer, a functional layer, a stress buffer layer and a corrosion-resistant layer, by optimizing material ratio and process parameters, such as ultrasonic dispersion, spin coating, vacuum sputtering and chemical vapor phase Deposition improves thermal conductivity and stress buffering capacity and reduces thermal shrinkage.

Benefits of technology

It significantly improves the heat dissipation performance and thermal stability of the semiconductor protective film, reduces the heat shrinkage problem caused by temperature changes, extends the service life of the protective film, and provides a more reliable protective effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005043175240000103
    Figure BDA0005043175240000103
  • Figure BDA0005043175240000111
    Figure BDA0005043175240000111
  • Figure BDA0005043175240000112
    Figure BDA0005043175240000112
Patent Text Reader

Abstract

The invention provides a semiconductor protective film and a coating process thereof. The semiconductor protective film comprises a substrate layer, a functional layer, a stress buffer layer and an anti-corrosion layer. The substrate layer is composed of vinyl chloride resin, polyimide resin, phenoxy resin and other raw materials; the functional layer comprises a heat dissipation medium, a stabilizer, a plasticizer and the like. The stress buffer layer is composed of a styrene-butadiene-styrene block copolymer, alpha-silicon dioxide and alpha-aluminum oxide according to a specific mass ratio, and the anti-corrosion layer is silicon nitride or silicon oxide. The heat dissipation medium, the stabilizer and other raw materials have specific composition and proportion. The coating process comprises the steps of ultrasonic cleaning, spin coating of the substrate layer, spraying of the functional layer, vacuum sputtering of the stress buffer layer, chemical vapor deposition of the anti-corrosion layer and the like. According to the protective film, the heat dissipation performance and the heat shrinkage performance of the semiconductor device are improved by optimizing the material ratio and the coating process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of manufacturing semiconductor devices, and in particular to a semiconductor protection film and a coating process thereof. Background Art

[0002] With the rapid development of semiconductor technology, the integration of semiconductor devices continues to increase, and the power density also increases, which puts higher requirements on the heat dissipation performance and thermal stability of semiconductor protective films. Although traditional semiconductor protective films can protect semiconductor devices from the erosion of the external environment to a certain extent, they still have significant defects in heat dissipation performance and thermal shrinkage performance.

[0003] In terms of heat dissipation performance, traditional semiconductor protective films are often unable to effectively dissipate the heat generated by semiconductor devices, causing heat to accumulate inside the device, leading to temperature rise, performance degradation, and even failure. This problem is particularly prominent in high-power, high-density semiconductor devices. In terms of thermal shrinkage performance, since semiconductor devices experience temperature changes during operation, and the materials of traditional protective films often do not match the thermal expansion coefficient of the semiconductor substrate, the protective film is prone to thermal shrinkage or deformation when the temperature changes, which in turn causes mechanical stress to the semiconductor device, affecting its stability and reliability. At the same time, after a period of use, the protective film shrinks at both ends, seriously affecting the service life and protection effect of the protective film. Summary of the invention

[0004] In view of this, the present invention proposes a semiconductor protection film and a coating process thereof to solve the above problems.

[0005] The technical solution of the present invention is achieved as follows: a semiconductor protective film: comprising a base layer, a functional layer, a stress buffer layer and an anti-corrosion layer; the base layer comprises the following raw materials in parts by weight: 30-50 parts of vinyl chloride resin, 25-35 parts of polyimide resin, 15-33 parts of phenoxy resin, 12-22 parts of polyethylene terephthalate, 10-20 parts of soybean oil, and 12-22 parts of calcium carbonate; the functional layer comprises the following raw materials in parts by weight: 5-10 parts of heat dissipation medium, 12-33 parts of stabilizer, and 20-40 parts of plasticizer; the stress buffer layer comprises styrene-butadiene-styrene block copolymer, α-silicon dioxide and α-aluminum oxide in a mass ratio of (14-25):(6-10):(2-5), and the anti-corrosion layer comprises but is not limited to silicon nitride or silicon oxide.

[0006] Furthermore, the base layer comprises the following raw materials in parts by weight: 40 parts of vinyl chloride resin, 30 parts of polyimide resin, 25 parts of phenoxy resin, 17 parts of polyethylene terephthalate, 15 parts of soybean oil, and 17 parts of calcium carbonate; the functional layer comprises the following raw materials in parts by weight: 8 parts of heat dissipation medium, 25 parts of stabilizer, and 30 parts of plasticizer; the stress buffer layer comprises styrene-butadiene-styrene block copolymer, α-silicon dioxide and α-alumina in a mass ratio of 20:8:3, and the anti-corrosion layer includes but is not limited to silicon nitride or silicon oxide.

[0007] Furthermore, the α-silicon dioxide and α-alumina are prepared by dispersing silicon dioxide or alumina in water, respectively, with a mass volume ratio of g / mL of 10-18:30, and ultrasonic dispersion, with an ultrasonic power of 500-1000W, a frequency of 15-25kHz, and ultrasonication for 20-60min. The obtained dispersion is mixed with a chromate solution with a mass concentration of 50-70%, stirred for 4-6h at a temperature of 12-22°C, and the volume ratio of the dispersion to the chromate solution is 1-3:1. The dispersion is dried to obtain α-silicon dioxide or α-alumina with a particle size of less than 0.5μm.

[0008] Furthermore, the heat dissipation medium is silicone grease, carbon fiber, and metal particles in a mass ratio of (6-12):(5-10):(3-8), the particle size of the heat dissipation medium is less than 10 μm, and the metal particles are selected from any one of copper, aluminum, nickel, chromium, and tungsten.

[0009] Furthermore, the stabilizer is dibutyltin dilaurate, calcium isooctanoate and boron nitride nanoparticles in a mass ratio of (4-9):(1-3):(8-12).

[0010] Furthermore, the plasticizer includes but is not limited to dibutyl phthalate, dioctyl phthalate, tricresyl phosphate, dioctyl adipate, and epoxy fatty acid methyl ester.

[0011] Furthermore, a coating process for a semiconductor protective film comprises the following steps:

[0012] Step A: Using ultrasonic waves to clean the semiconductor surface to remove pollutants and impurities on the surface of the semiconductor substrate;

[0013] Step B: mixing the raw materials for the base layer, spin coating on the surface of the semiconductor substrate at a spin rate of 5000-8000 rpm, and drying at 80-120° C. to form a base layer with a thickness of 10-50 μm;

[0014] Step C: spraying the functional layer raw material on the upper surface of the base layer to form a functional layer with a thickness of 5-20 μm;

[0015] Step D: sputtering a stress buffer layer material on the functional layer by a vacuum sputtering process to form a stress buffer layer with a thickness of 5-10 μm;

[0016] Step E: placing the semiconductor substrate with the stress buffer layer formed thereon into a chemical vapor deposition reaction chamber, introducing silane and ammonia or oxygen for deposition, and obtaining an anti-corrosion layer with a thickness of 3-10 μm.

[0017] Step F: Drying and curing at a temperature of 100-200° C. for 30-60 minutes to obtain a semiconductor protection film.

[0018] Furthermore, the spray gun pressure of the spraying in step C is 0.2-0.4 MPa, the spraying distance is 15-25 cm, the coating flow rate is 50-100 mL / min, the spray gun speed is 0.1-1 m / s, and the spraying temperature is 15-30°C.

[0019] Furthermore, the parameters of the sputtering process in step D are: sputtering power is 300-500W, sputtering pressure is 0.1-0.5Pa, and sputtering time is 25-45min.

[0020] Furthermore, in the step E, the RF power in the chemical vapor deposition reaction chamber is 100-300 W, the temperature is 300-1200° C., the reaction gas pressure is 10-100 Pa, the silane flow rate is 50-100 sccm, and the ammonia or oxygen flow rate is 50-300 sccm.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The scheme of the present invention optimizes the material ratio and coating process of the semiconductor protective film, especially introduces a heat dissipation medium and a stress buffer layer of a specific ratio; through the heat dissipation medium of a reasonable ratio, the thermal conductivity of the semiconductor protective film is effectively improved, the thermal radiation capacity of the film is enhanced, the heat is dissipated in the form of thermal radiation, the operating temperature of the device is reduced, and the device performance is stable; the stress buffer layer and the optimized combination of the materials of each layer absorb and disperse the stress generated by the mismatch of the thermal expansion coefficient, effectively reduce the thermal shrinkage rate of the semiconductor protective film at different temperatures, so that it can maintain dimensional stability in a wide temperature range, avoid deformation, cracking or separation of the protective film from the semiconductor device caused by thermal shrinkage, and improve the long-term protection effect of the protective film on the semiconductor device. The setting of the anti-corrosion layer, using materials such as silicon nitride or silicon oxide, can effectively prevent the erosion of the semiconductor device by external corrosive substances, provide reliable protection for the semiconductor device, and enable it to work stably in harsh environments.

[0023] The base layer, functional layer, stress buffer layer and anti-corrosion layer cooperate with each other to give full play to their respective functional advantages, so that the semiconductor protection film has comprehensive high performance and can meet the protection needs of semiconductor devices under complex working conditions.

[0024] The coating process in the scheme of the present invention adopts ultrasonic cleaning, spin coating, spraying, vacuum sputtering and chemical vapor deposition and other technical means to optimize the coating process, realize the precise control and efficient preparation of each layer of the semiconductor protective film, and reduce the local shrinkage caused by uneven coating, poor adhesion and poor edge coverage.

[0025] The protective film and coating process thereof of the present invention are intended to significantly improve the heat dissipation performance of semiconductor devices and reduce the thermal shrinkage problem caused by temperature changes, thereby providing strong support for the further development of semiconductor technology. DETAILED DESCRIPTION

[0026] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0027] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0028] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0029] Example 1

[0030] A semiconductor protective film: comprising a base layer, a functional layer, a stress buffer layer and an anti-corrosion layer;

[0031] The base layer comprises the following raw materials in parts by weight: 30 parts of vinyl chloride resin, 25 parts of polyimide resin, 15 parts of phenoxy resin, 12 parts of polyethylene terephthalate, 10 parts of soybean oil, and 12 parts of calcium carbonate;

[0032] The functional layer comprises the following raw materials in parts by weight: 5 parts of heat dissipation medium, 12 parts of stabilizer, and 20 parts of plasticizer; the heat medium is silicone grease, carbon fiber, and copper metal particles in a mass ratio of 6:5:3, and the particle size of the heat dissipation medium is less than 10 μm; the stabilizer is dibutyltin dilaurate, calcium isooctanoate, and boron nitride nanoparticles in a mass ratio of 4:1:8; the plasticizer is dibutyl phthalate;

[0033] The stress buffer layer comprises a styrene-butadiene-styrene block copolymer, α-silicon dioxide and α-alumina in a mass ratio of 14:6:2; the α-silicon dioxide and α-alumina are prepared by dispersing silicon dioxide or alumina in water, respectively, with a mass volume ratio of g / mL of 10:30, and ultrasonic dispersion, with an ultrasonic power of 500W, a frequency of 15kHz, and ultrasonication for 20 minutes, and mixing the obtained dispersion with a chromate solution with a mass concentration of 50%, stirring for 4 hours at a temperature of 12°C, with a volume ratio of the dispersion to the chromate solution of 1:1, and drying to obtain α-silicon dioxide or α-alumina with a particle size of less than 0.5 μm;

[0034] The anti-corrosion layer is silicon nitride.

[0035] Example 2

[0036] A semiconductor protective film: comprising a base layer, a functional layer, a stress buffer layer and an anti-corrosion layer;

[0037] The base layer comprises the following raw materials in parts by weight: 50 parts of vinyl chloride resin, 35 parts of polyimide resin, 33 parts of phenoxy resin, 22 parts of polyethylene terephthalate, 20 parts of soybean oil, and 22 parts of calcium carbonate;

[0038] The functional layer comprises the following raw materials in parts by weight: 10 parts of heat dissipation medium, 33 parts of stabilizer, and 40 parts of plasticizer; the heat medium is silicone grease, carbon fiber, and aluminum metal particles in a mass ratio of 12:10:8, and the particle size of the heat dissipation medium is less than 10 μm; the stabilizer is dibutyltin dilaurate, calcium isooctanoate, and boron nitride nanoparticles in a mass ratio of 9:3:12; the plasticizer is dioctyl phthalate;

[0039] The stress buffer layer comprises a styrene-butadiene-styrene block copolymer, α-silicon dioxide and α-alumina in a mass ratio of 25:10:5; the α-silicon dioxide and α-alumina are prepared by dispersing silicon dioxide or alumina in water, respectively, with a mass volume ratio of g / mL of 18:30, and ultrasonic dispersion, with an ultrasonic power of 1000W, a frequency of 25kHz, and ultrasonication for 60 minutes, to obtain a dispersion liquid and a chromate solution with a mass concentration of 70%, and stirring for 6 hours at a temperature of 22°C, wherein the volume ratio of the dispersion liquid to the chromate solution is 3:1, and drying is performed to obtain α-silicon dioxide or α-alumina with a particle size of less than 0.5 μm;

[0040] The anti-corrosion layer is silicon nitride.

[0041] Example 3

[0042] A semiconductor protective film: comprising a base layer, a functional layer, a stress buffer layer and an anti-corrosion layer; the base layer comprises the following raw materials in parts by weight: 40 parts of vinyl chloride resin, 30 parts of polyimide resin, 25 parts of phenoxy resin, 17 parts of polyethylene terephthalate, 15 parts of soybean oil and 17 parts of calcium carbonate;

[0043] The functional layer comprises the following raw materials in parts by weight: 8 parts of heat dissipation medium, 25 parts of stabilizer, and 30 parts of plasticizer; the heat dissipation medium is silicone grease, carbon fiber, and metal particles in a mass ratio of 9:8:5, the particle size of the heat dissipation medium is less than 10 μm, and the metal particles are selected from copper metal particles; the stabilizer is dibutyltin dilaurate, calcium isooctanoate, and boron nitride nanoparticles in a mass ratio of 7:2:10; the plasticizer is selected from tricresyl phosphate;

[0044] The stress buffer layer comprises a styrene-butadiene-styrene block copolymer, α-silicon dioxide and α-alumina in a mass ratio of 20:8:3. The α-silicon dioxide and α-alumina are prepared by dispersing silicon dioxide or alumina in water, respectively, with a mass volume ratio of g / mL of 15:30, and ultrasonic dispersion with an ultrasonic power of 800W, a frequency of 20kHz, and ultrasonication for 40 minutes. The obtained dispersion is mixed with a chromate solution with a mass concentration of 60%, stirred for 5 hours at a temperature of 17°C, and the volume ratio of the dispersion to the chromate solution is 2:1. The dispersion is dried to obtain α-silicon dioxide or α-alumina with a particle size of less than 0.5 μm.

[0045] The anti-corrosion layer is silicon nitride;

[0046] The above-mentioned embodiments 1-3 adopt the following coating process:

[0047] Step A: Using ultrasonic waves to clean the semiconductor surface to remove pollutants and impurities on the surface of the semiconductor substrate;

[0048] Step B: mixing the raw materials for the base layer, spin coating on the surface of the semiconductor substrate at a spin rate of 7000 rpm, and drying at 100° C. to form a base layer with a thickness of 30 μm;

[0049] Step C: spraying the functional layer raw material on the upper surface of the base layer to form a functional layer with a thickness of 15 μm; the spray gun pressure is 0.3 MPa, the spray distance is 20 cm, the coating flow rate is 80 mL / min, the spray gun speed is 0.5 m / s, and the spray temperature is 22°C;

[0050] Step D: sputtering a stress buffer layer material on the functional layer by a vacuum sputtering process to form a stress buffer layer with a thickness of 8 μm; the sputtering power is 400 W, the sputtering pressure is 0.3 Pa, and the sputtering time is 35 min;

[0051] Step E: Place the semiconductor substrate with the stress buffer layer formed into a chemical vapor deposition reaction chamber, introduce silane and ammonia, the RF power is 200W, the temperature is 700°C, the reaction gas pressure is 50Pa, the silane flow rate is 80sccm, and the ammonia flow rate is 200sccm, and deposition is performed to obtain a silicon nitride anti-corrosion layer with a thickness of 8μm.

[0052] Step F: Dry and cure at 150° C. for 50 minutes to obtain a semiconductor protection film.

[0053] Example 4

[0054] A semiconductor protective film: comprising a base layer, a functional layer, a stress buffer layer and an anti-corrosion layer; the base layer comprises the following raw materials in parts by weight: 40 parts of vinyl chloride resin, 30 parts of polyimide resin, 25 parts of phenoxy resin, 17 parts of polyethylene terephthalate, 15 parts of soybean oil and 17 parts of calcium carbonate;

[0055] The functional layer comprises the following raw materials in parts by weight: 8 parts of heat dissipation medium, 25 parts of stabilizer, and 30 parts of plasticizer; the heat dissipation medium is silicone grease, carbon fiber, and metal particles in a mass ratio of 9:8:5, the particle size of the heat dissipation medium is less than 10 μm, and the metal particles are selected from copper metal particles; the stabilizer is dibutyltin dilaurate, calcium isooctanoate, and boron nitride nanoparticles in a mass ratio of 7:2:10; the plasticizer is selected from tricresyl phosphate;

[0056] The stress buffer layer comprises a styrene-butadiene-styrene block copolymer, α-silicon dioxide and α-alumina in a mass ratio of 20:8:3. The α-silicon dioxide and α-alumina are prepared by dispersing silicon dioxide or alumina in water, respectively, with a mass volume ratio of g / mL of 15:30, and ultrasonic dispersion with an ultrasonic power of 800W, a frequency of 20kHz, and ultrasonication for 40 minutes. The obtained dispersion is mixed with a chromate solution with a mass concentration of 60%, stirred for 5 hours at a temperature of 17°C, and the volume ratio of the dispersion to the chromate solution is 2:1. The dispersion is dried to obtain α-silicon dioxide or α-alumina with a particle size of less than 0.5 μm.

[0057] The anti-corrosion layer is silicon oxide;

[0058] The above-mentioned embodiment 4 adopts the following coating process:

[0059] Step A: Using ultrasonic waves to clean the semiconductor surface to remove pollutants and impurities on the surface of the semiconductor substrate;

[0060] Step B: mixing the raw materials for the base layer, spin coating on the surface of the semiconductor substrate at a spin rate of 5000 rpm, and drying at 80° C. to form a base layer with a thickness of 10 μm;

[0061] Step C: spraying the functional layer raw material on the upper surface of the base layer to form a functional layer with a thickness of 5 μm, a spray gun pressure of 0.2 MPa, a spray distance of 15 cm, a coating flow rate of 50 mL / min, a spray gun speed of 0.1 m / s, and a spray temperature of 15°C;

[0062] Step D: sputtering a stress buffer layer material on the functional layer by a vacuum sputtering process, with a sputtering power of 300 W, a sputtering pressure of 0.1 Pa, and a sputtering time of 25 min to form a stress buffer layer with a thickness of 5 μm;

[0063] Step E: Place the semiconductor substrate with the stress buffer layer formed into a chemical vapor deposition reaction chamber, introduce silane and oxygen, the RF power is 100W, the temperature is 300°C, the reaction gas pressure is 10Pa, the silane flow rate is 50sccm, and the oxygen flow rate is 50sccm. Deposition is performed to obtain a silicon oxide anti-corrosion layer with a thickness of 3μm.

[0064] Step F: Dry and cure at 100° C. for 30 minutes to obtain a semiconductor protection film.

[0065] Example 5

[0066] A semiconductor protective film: comprising a base layer, a functional layer, a stress buffer layer and an anti-corrosion layer; the base layer comprises the following raw materials in parts by weight: 40 parts of vinyl chloride resin, 30 parts of polyimide resin, 25 parts of phenoxy resin, 17 parts of polyethylene terephthalate, 15 parts of soybean oil and 17 parts of calcium carbonate;

[0067] The functional layer comprises the following raw materials in parts by weight: 8 parts of heat dissipation medium, 25 parts of stabilizer, and 30 parts of plasticizer; the heat dissipation medium is silicone grease, carbon fiber, and metal particles in a mass ratio of 9:8:5, the particle size of the heat dissipation medium is less than 10 μm, and the metal particles are selected from copper metal particles; the stabilizer is dibutyltin dilaurate, calcium isooctanoate, and boron nitride nanoparticles in a mass ratio of 7:2:10; the plasticizer is selected from tricresyl phosphate;

[0068] The stress buffer layer comprises a styrene-butadiene-styrene block copolymer, α-silicon dioxide and α-alumina in a mass ratio of 20:8:3. The α-silicon dioxide and α-alumina are prepared by dispersing silicon dioxide or alumina in water, respectively, with a mass volume ratio of g / mL of 15:30, and ultrasonic dispersion with an ultrasonic power of 800W, a frequency of 20kHz, and ultrasonication for 40 minutes. The obtained dispersion is mixed with a chromate solution with a mass concentration of 60%, stirred for 5 hours at a temperature of 17°C, and the volume ratio of the dispersion to the chromate solution is 2:1. The dispersion is dried to obtain α-silicon dioxide or α-alumina with a particle size of less than 0.5 μm.

[0069] The anti-corrosion layer is silicon oxide;

[0070] The above-mentioned embodiment 5 adopts the following coating process:

[0071] Step A: Using ultrasonic waves to clean the semiconductor surface to remove pollutants and impurities on the surface of the semiconductor substrate;

[0072] Step B: mixing the raw materials for the base layer, spin coating on the surface of the semiconductor substrate at a spin rate of 8000 rpm, and drying at 120° C. to form a base layer with a thickness of 50 μm;

[0073] Step C: spraying the functional layer raw material on the upper surface of the base layer to form a functional layer with a thickness of 20 μm; the spray gun pressure is 0.4 MPa, the spray distance is 25 cm, the coating flow rate is 100 mL / min, the spray gun speed is 1 m / s, and the spray temperature is 30°C;

[0074] Step D: sputtering a stress buffer layer material on the functional layer by a vacuum sputtering process to form a stress buffer layer with a thickness of 10 μm; the sputtering power is 500 W, the sputtering pressure is 0.5 Pa, and the sputtering time is 45 min;

[0075] Step E: Place the semiconductor substrate with the stress buffer layer formed into a chemical vapor deposition reaction chamber, introduce silane and oxygen, the RF power is 300W, the temperature is 1200°C, the reaction gas pressure is 100Pa, the silane flow rate is 100sccm, and the oxygen flow rate is 300sccm, and deposition is performed to obtain a silicon oxide anti-corrosion layer with a thickness of 10μm.

[0076] Step F: Dry and cure at 200° C. for 60 minutes to obtain a semiconductor protection film.

[0077] Comparative Example 1

[0078] The difference between this comparative example and Example 3 is that a semiconductor protective film comprises a base layer, a functional layer, a stress buffer layer and an anti-corrosion layer; the base layer comprises the following raw materials in parts by weight: 10 parts of vinyl chloride resin, 40 parts of polyimide resin, 45 parts of phenoxy resin, 10 parts of polyethylene terephthalate, 5 parts of soybean oil, and 8 parts of calcium carbonate; the functional layer comprises the following raw materials in parts by weight: 2 parts of heat dissipation medium, 10 parts of stabilizer, and 12 parts of plasticizer.

[0079] Comparative Example 2

[0080] The difference between this comparative example and Example 3 is that no heat dissipation medium is added to the functional layer.

[0081] Comparative Example 3

[0082] The difference between this comparative example and Example 3 is that no stabilizer is added to the functional layer.

[0083] Comparative Example 4

[0084] The difference between this comparative example and Example 3 is that the semiconductor protection film is not coated with a stress buffer layer.

[0085] Comparative Example 5

[0086] The difference between this comparative example and Example 3 is that in the coating process of the semiconductor protection film, the functional layer and the stress buffer layer are both coated by spraying, specifically:

[0087] Step A: Using ultrasonic waves to clean the semiconductor surface to remove pollutants and impurities on the surface of the semiconductor substrate;

[0088] Step B: mixing the raw materials for the base layer, spin coating on the surface of the semiconductor substrate at a spin rate of 7000 rpm, and drying at 100° C. to form a base layer with a thickness of 30 μm;

[0089] Step C: spraying the functional layer raw material on the upper surface of the base layer to form a functional layer with a thickness of 15 μm, spraying the stress buffer layer material to form a stress buffer layer with a thickness of 8 μm; the spray gun pressure is 0.3 MPa, the spray distance is 20 cm, the coating flow rate is 80 mL / min, the spray gun speed is 0.5 m / s, and the spray temperature is 22°C;

[0090] Step E: Place the semiconductor substrate with the stress buffer layer formed into a chemical vapor deposition reaction chamber, introduce silane and ammonia, the RF power is 200W, the temperature is 700°C, the reaction gas pressure is 50Pa, the silane flow rate is 80sccm, and the ammonia flow rate is 200sccm, and deposition is performed to obtain a silicon nitride anti-corrosion layer with a thickness of 8μm.

[0091] Step F: Dry and cure at 150° C. for 50 minutes to obtain a semiconductor protection film.

[0092] Test Example 1-Heat Dissipation Performance

[0093] The semiconductor protection films coated with the above-mentioned Examples 1-5 and Comparative Examples 1-5 were tested for their heat dissipation performance, including thermal resistance, thermal diffusion coefficient, thermal conductivity and maximum surface temperature.

[0094] 1. Thermal resistance test

[0095] (1) Experimental steps: Place the sample coated with semiconductor protective film between the heating stage and the heat sink. Install heat flow meters and thermocouples on the upper and lower surfaces of the sample to measure heat flow and temperature. Turn on the heating stage and set the heating power to 1200W. When the system reaches thermal stability (temperature and heat flow no longer change with time), record the heat flow Q measured by the heat flow meter and the temperature difference ΔT measured by the thermocouples on the upper and lower surfaces through the data acquisition system.

[0096] (2) Thermal resistance calculation formula: (where R is thermal resistance, ΔT is temperature difference, and Q is heat flow) Calculate thermal resistance.

[0097] 2. Thermal diffusivity test

[0098] (1) Experimental steps: Prepare the sample into a thin sheet and ensure that the surface is flat and smooth. Place the sample in the sample chamber of the laser flash thermal diffusion coefficient tester so that its front surface faces the laser beam. Start the laser to irradiate the front surface of the sample, and use an infrared detector to monitor the temperature change of the back surface of the sample. The instrument records the change of surface temperature over time, and calculates the thermal diffusion coefficient based on the relevant model and formula through data processing software.

[0099] 3. Thermal conductivity test

[0100] (1) Experimental steps:

[0101] Place the sample between the hot plate and the cold plate and fix it with a clamp. Install temperature sensors and heat flow meters on the hot plate, the cold plate and inside the sample. Turn on the temperature control system of the hot plate and the cold plate to form a stable temperature difference between the hot plate and the cold plate. When the system reaches a steady state, record the heat flux Q measured by the heat flow meter, the temperature difference ΔT on both sides of the sample, the thickness d and the area A of the sample.

[0102] (2) Thermal conductivity calculation formula: (where k is thermal conductivity, Q is heat flow, d is sample thickness, A is sample area, and ΔT is temperature difference)

[0103] The thermal conductivity is calculated according to the above formula.

[0104] 4. Maximum surface temperature (°C) test: Use an infrared thermal imager to photograph the sample surface, analyze the thermal imaging image, and obtain the maximum temperature value of the sample surface.

[0105] 5. Test results:

[0106] Table 1:

[0107]

[0108]

[0109] From the above results, it can be seen that the thermal resistance value of the embodiment group is between 0.15 and 0.26 K / W, which is relatively low, indicating that the materials in these embodiments have good heat transfer ability, which may be because their internal structure is conducive to the rapid conduction of heat; the thermal diffusion coefficient is between 0.34 and 0.38, which is relatively high, indicating that heat can diffuse rapidly in these materials, which is conducive to the uniform distribution of heat; the thermal conductivity is between 1.30 and 1.40, showing good thermal conductivity, indicating that the protective film can effectively conduct heat, and the maximum surface temperature is between 35 and 38 ° C, which is relatively low and stable, indicating that these materials can effectively control the temperature rise under the test conditions.

[0110] Test Example 2-Heat Shrinkage Test

[0111] 1. Sample preparation: Cut rectangular samples of 100 mm × 100 mm from the substrates coated with semiconductor protective films in Example 3 and Comparative Examples 2-5, select three different positions on the samples to measure the initial length (L0) and width (W0), and record the measured values.

[0112] 2. Heat shrinkage treatment: Place the sample flat on a clean metal mesh or ceramic tray, and then put it into a precision oven preheated to the set temperature of 50℃, 100℃, 150℃, 200℃, and keep it for 1-2 hours.

[0113] 3. Cooling and measurement: Take out the sample and cool it to room temperature (about 25°C) for 30-60 minutes. After the sample has cooled, measure the length (L1) and width (W1) of the sample again.

[0114] 4. The thermal shrinkage rate is calculated according to the following formula:

[0115]

[0116] 5. Test results

[0117] Table 2: Longitudinal heat shrinkage

[0118]

[0119] Table 3: Transverse heat shrinkage

[0120]

[0121] According to the above results and the test data of the longitudinal heat shrinkage rate and the transverse heat shrinkage rate, the heat shrinkage rate of the semiconductor protection film of Example 3 under different temperature conditions is significantly lower than that of Comparative Examples 2-5, indicating that the semiconductor protection film of Example 3 has better performance in terms of stability, can better adapt to the working requirements under different temperature environments, and reduce the performance changes and potential failure risks caused by heat shrinkage.

[0122] The material of Example 3 shows better performance than the comparative example in terms of heat dissipation performance and thermal shrinkage rate.

[0123] Compared with comparative example 1, example 3 shows that the raw materials of the protective film of the present invention can achieve better heat dissipation performance under a specific ratio.

[0124] Compared with Comparative Example 2, Example 3 of the present invention selects silicone grease, carbon fiber, and metal particles in a reasonable ratio as heat dissipation media, which can synergistically improve heat dissipation efficiency, improve thermal cycle stability, reduce thermal resistance, etc. The silicone grease provides efficient thermal conductivity and electrical isolation functions; the carbon fiber provides excellent thermal conductivity and mechanical strength; the metal particles improve electrical conductivity, thermal conductivity, hardness and wear resistance of the protective film.

[0125] Compared with Comparative Example 3, the stabilizer made of dibutyltin dilaurate, calcium isooctanoate and boron nitride nanoparticles, dibutyltin dilaurate, can absorb and neutralize harmful substances such as hydrogen chloride generated by thermal decomposition during the processing and use of the semiconductor protective film, inhibit the dehydrochlorination reaction, thereby improving the thermal stability of the semiconductor protective film, and can also coordinate with the active sites in the polymer molecular chain to form a stable complex, thereby limiting the movement and thermal vibration of the molecular chain, reducing the conformational change and thermal shrinkage behavior of the molecular chain when heated; calcium isooctanoate can react with hydrogen chloride to form a stable compound, reducing the effect of hydrogen chloride on the polymer chain. The catalytic degradation of the semiconductor protective film can delay the decomposition and aging process of the semiconductor protective film when heated, improve its long-term thermal stability, and reduce the thermal shrinkage of the semiconductor protective film; Boron nitride nanoparticles have excellent thermal stability and high temperature tolerance. When evenly dispersed in the semiconductor protective film, they can form a physical barrier to hinder the transfer of heat and the movement of molecular chains, reduce the degradation and cross-linking reaction of molecular chains under thermal action, thereby improving the overall thermal stability of the semiconductor protective film and reducing the thermal expansion and thermal contraction of molecular chains caused by heat accumulation; the three together can significantly improve the thermal stability of the semiconductor protective film and prevent thermal degradation and performance degradation at high temperatures.

[0126] Compared with Example 4, Example 3 adds a stress buffer layer between the functional layer and the anti-corrosion layer, which can reduce the internal stress generated in the functional layer and the anti-corrosion layer, and the destructive effect on the two-layer structure, improve the bonding strength and adhesion between the two layers, prevent the occurrence of interlayer separation or peeling, and improve the overall stability of the semiconductor protective film; at the same time, the stress buffer layer can coordinate the thermal expansion difference between the two layers to a certain extent through its lower elastic modulus and higher thermal expansion coefficient, reduce the generation of thermal stress, and improve thermal stability.

[0127] Among them, the combined action of styrene-butadiene-styrene block copolymer, α-silicon dioxide and α-alumina can more effectively disperse and buffer the stress generated by the semiconductor during coating. The modified α-silicon dioxide and α-alumina have better thermal stability, and can effectively absorb and disperse the stress generated by semiconductor devices under temperature changes or mechanical stress, preventing the influence of thermal damage on semiconductor devices.

[0128] Compared with Example 5, the use of chemical vapor deposition to coat the stress buffer layer in the preparation of the semiconductor protective film can achieve uniform deposition on a complex three-dimensional surface, ensuring that the stress buffer layer is evenly covered to form a coating with good conformality; it can form a tight chemical bond and physical adsorption with the functional layer and the anti-corrosion layer, thereby establishing a good interface bond between the layers. This strong interface bond helps to improve the adhesion and synergy between the layers, reduce the risk of interlayer separation, peeling or interface failure, and ensure the structural integrity and performance stability of the semiconductor protective film during long-term use; chemical vapor deposition coating can accurately control the deposition thickness of the stress buffer layer. By adjusting the deposition parameters (such as reaction gas flow, deposition time, temperature and pressure, etc.), a stress buffer layer with a specific thickness can be prepared to reduce the problem of local shrinkage caused by uneven coating.

[0129] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A semiconductor protection film, characterized in that: It includes a base layer, a functional layer, a stress buffer layer and an anti-corrosion layer; the base layer includes the following raw materials in parts by weight: 30-50 parts of vinyl chloride resin, 25-35 parts of polyimide resin, 15-33 parts of phenoxy resin, 12-22 parts of polyethylene terephthalate, 10-20 parts of soybean oil, and 12-22 parts of calcium carbonate; the functional layer includes the following raw materials in parts by weight: 5-10 parts of heat dissipation medium, 12-33 parts of stabilizer, and 20-40 parts of plasticizer; the stress buffer layer includes styrene-butadiene-styrene block copolymer, α-silicon dioxide and α-aluminum oxide in a mass ratio of (14-25):(6-10):(2-5), and the anti-corrosion layer includes but is not limited to silicon nitride or silicon oxide.

2. A semiconductor protection film according to claim 1, characterized in that: The base layer comprises the following raw materials in parts by weight: 40 parts of vinyl chloride resin, 30 parts of polyimide resin, 25 parts of phenoxy resin, 17 parts of polyethylene terephthalate, 15 parts of soybean oil, and 17 parts of calcium carbonate; the functional layer comprises the following raw materials in parts by weight: 8 parts of heat dissipation medium, 25 parts of stabilizer, and 30 parts of plasticizer; the stress buffer layer comprises styrene-butadiene-styrene block copolymer, α-silicon dioxide, and α-alumina in a mass ratio of 20:8:3, and the anti-corrosion layer includes but is not limited to silicon nitride or silicon oxide.

3. A semiconductor protection film according to claim 1 or 2, characterized in that: The α-silicon dioxide and α-alumina are prepared by dispersing silicon dioxide or alumina in water respectively, with a mass volume ratio of g / mL of 10-18:30, and ultrasonic dispersion, with an ultrasonic power of 500-1000W, a frequency of 15-25kHz, and ultrasonication for 20-60min. The obtained dispersion is mixed with a chromate solution with a mass concentration of 50-70%, and stirred for 4-6h at a temperature of 12-22°C, with a volume ratio of the dispersion to the chromate solution of 1-3:1, and dried to obtain α-silicon dioxide or α-alumina with a particle size of less than 0.5μm.

4. A semiconductor protection film according to claim 1, characterized in that: The heat dissipation medium is silicone grease, carbon fiber, and metal particles in a mass ratio of (6-12):(5-10):(3-8). The particle size of the heat dissipation medium is less than 10 μm, and the metal particles are selected from any one of copper, aluminum, nickel, chromium, and tungsten.

5. A semiconductor protection film according to claim 1, characterized in that: The stabilizer is dibutyltin dilaurate, calcium isooctanoate and boron nitride nanoparticles in a mass ratio of (4-9):(1-3):(8-12).

6. A semiconductor protection film according to claim 1, characterized in that: The plasticizer includes, but is not limited to, dibutyl phthalate, dioctyl phthalate, tricresyl phosphate, dioctyl adipate, and epoxy fatty acid methyl ester.

7. A semiconductor protection film coating process as claimed in claim 1, characterized in that: The following steps are included Step A: Using ultrasonic waves to clean the semiconductor surface to remove pollutants and impurities on the surface of the semiconductor substrate; Step B: mixing the raw materials for the base layer, spin coating on the surface of the semiconductor substrate at a spin rate of 5000-8000 rpm, and drying at 80-120° C. to form a base layer with a thickness of 10-50 μm; Step C: spraying the functional layer raw material on the upper surface of the base layer to form a functional layer with a thickness of 5-20 μm; Step D: sputtering a stress buffer layer material on the functional layer by a vacuum sputtering process to form a stress buffer layer with a thickness of 5-10 μm; Step E: placing the semiconductor substrate with the stress buffer layer formed thereon into a chemical vapor deposition reaction chamber, introducing silane and ammonia or oxygen for deposition to obtain an anti-corrosion layer with a thickness of 3-10 μm. Step F: Drying and curing at a temperature of 100-200° C. for 30-60 minutes to obtain a semiconductor protection film.

8. A semiconductor protection film coating process as claimed in claim 1, characterized in that: The spray gun pressure of the spraying in step C is 0.2-0.4 MPa, the spraying distance is 15-25 cm, the coating flow rate is 50-100 mL / min, the spray gun speed is 0.1-1 m / s, and the spraying temperature is 15-30°C.

9. A semiconductor protection film coating process as claimed in claim 1, characterized in that: The parameters of the sputtering process in step D are: sputtering power is 300-500W, sputtering pressure is 0.1-0.5Pa, and sputtering time is 25-45min.

10. A semiconductor protection film coating process as claimed in claim 1, characterized in that: In the step E, the radio frequency power in the chemical vapor deposition reaction chamber is 100-300 W, the temperature is 300-1200° C., the reaction gas pressure is 10-100 Pa, the silane flow rate is 50-100 sccm, and the ammonia or oxygen flow rate is 50-300 sccm.

Citation Information

Patent Citations

  • Organic light-emitting device and preparation method thereof

    CN103730598A

  • IGBT power module heat dissipation structure and method for improving large-area welding reliability

    CN112687633A

  • Packaging structure and packaging method thereof, and display device

    CN113130810A

  • Multi-layer ceramic-based composite thermal protection coating as well as preparation method and application thereof

    CN113800955A

  • Multi-layer coating for corrosion resistance

    CN118843926A